Antibody–drug conjugates nonclinical support: from early to late nonclinical bioanalysis using ligand-binding assays. (July 2015) - Kumar, Seema; King, Lindsay E; Clark, Tracey H; Gorovits, Boris
Seema Kumar is a Principal Scientist at Pfizer. She leads a group that provides regulated bioanalytical support including assay development, validation and sample analysis for the PK and immunogenicity assessment for preclinical and clinical development of Pfizer's biotherapeutics portfolio. She is also responsible for scientific oversight of regulated studies outsourced at CROs. Prior to Pfizer, Dr Kumar held a similar role as Director of CLIA certified Clinical Bioanalytical Laboratory at XBiotech USA, Inc. She holds a PhD in Biophysical Chemistry from Johns Hopkins University, and has published several publications in peer-reviewed journals, and contributed to book chapters. The objective of antibody–drug conjugate (ADC) bioanalysis at different stages of drug development may vary and so are the associated bioanalytical challenges. While at early drug discovery stage involving candidate selection, optimization and preliminary nonclinical assessments, the goal of ADC bioanalysis is to provide PK, toxicity and efficacy data that assists in the design and selection of potential drug candidates, the late nonclinical and clinical drug development stage typically involves regulated ADC bioanalysis that delivers TK data to define and understand pharmacological and toxicological properties of the lead ADC candidate. Bioanalytical strategies and considerations involved in developing successful ligand binding assays for ADC characterization from early discovery to late nonclinical stages of drug development are presented here.